2020
DOI: 10.3846/btp.2020.12657
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Roles of Pro-Commitment to Learning and Adaptability to Technological Change: Professional Experience Portfolio Toward Employee Performance

Abstract: To overcome the problem of declining performance, organizations need a variety of professional experience portfolio and strong pro-commitment to learning in addition to the need for employees to adapt to various changes, especially technological changes. Adopting the role of organizational learning theory and human capital, this study aims to analyse the pro-commitment to learning and adaptability to change whether it is able to mediate the influence of the professional experience portfolio on employee perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
1
0
1
Order By: Relevance
“…The study concluded that dynamic managerial capability that includes managerial social capital and managerial cognition promote market orientation and financial performance of the firms. In addition, Wulandari et al (2020) reported a positive effect of human capital factors such as procommitment to learn and adaptability to technological change on performance.…”
Section: Analysis Of Bibliographic Couplingmentioning
confidence: 99%
“…The study concluded that dynamic managerial capability that includes managerial social capital and managerial cognition promote market orientation and financial performance of the firms. In addition, Wulandari et al (2020) reported a positive effect of human capital factors such as procommitment to learn and adaptability to technological change on performance.…”
Section: Analysis Of Bibliographic Couplingmentioning
confidence: 99%
“…Penggunaan teknologi akan meningkatkan daya saing, peningkatan sumber daya, peningkatan efektivitas usaha, serta peningkatan kinerja organisasi. Hal ini juga dipertegas oleh hasil penelitian terdahulu dari Adeyeye et al (2013), Anggono (2015), Chege & Wang (2020), serta (Wulandari & Dwiatmadja (2020) bahwa perubahan teknologi berpengaruh positif terhadap kinerja organisasi. Inovasi teknologi merupakan hal yang sangat penting bagi keberlanjutan organisasi dan penentu competitive advantage organisasi (Azubuike, 2013).…”
Section: Hipotesis 221 Pengaruh Positif Perubahan Teknologi Terhadap ...unclassified
“…Studies have been conducted on the competencies of managers at Payame Noor University (Godarzi & Soltani, 2017), research-oriented organizational managers (Panahi et al, 2018), city service organization managers (Jamshidi Kohsari et al, 2016), and managers of national projects (Taslimi et al, 2013) are examples of such studies at the national level. Internationally, studies have included educational institution managers (Shukhratovich, 2022), professional experiences and competencies required by managers in Islamic countries (Wulandari & Dwiatmadja, 2020), sports and physical education coaches (Jonni, 2019), healthcare service managers (Liang et al, 2018), hospital leaders (Shum et al, 2018), manufacturing industry managers (Steyn & Van Staden, 2018), nursing managers (Goktepe et al, 2018), hotel industry managers (Wong & Lee, 2017), educational managers (Astereki et al, 2022), and primary school managers (Bafadal et al, 2019).…”
mentioning
confidence: 99%